Biophysical connectivity of snapper spawning aggregations and marine protected area management alternatives in Cuba. (29th August 2018) - Claro, Rodolfo; Lindeman, Kenyon C.; Kough, Andrew S.; Paris, Claire B.
Abstract: The ability of larvae to move beyond the spatial range of adult migrations can be critical to the resilience of populations that aggregate to spawn. We reviewed the literature and unpublished information on larval transport modeling, reef fish spawning aggregations, and marine protected area (MPA) management to identify alternatives for Cuban spawning site conservation. Larval transport information is available at annual and decadal scales for eight Cuban sites for five species of snappers. Connectivity patterns were examined: (a) within Cuban regions, (b) among Cuban regions, and (c) among other countries. We compared this information with the distribution of protected areas relative to spawning sites, site management attributes, and potential alternatives. Of eight focal spawning sites, seven are in protected areas and one is proposed. Southeast and north‐central Cuba had highest estimated within‐region retention levels. Southwest and northwest sites exported relatively more larvae out‐of‐region. Southern regions produced larvae that reached Jamaica, the Cayman Islands and Haiti. All northern regions can export larvae to the southern Bahamas. The regions and sites within are geomorphologically diverse with variable fishing and socio‐economic attributes. Information on stock status and protected area efficacy is limited and field assessments of aggregation status are needed for multispecies spawning sites. Few management plans address spawning conservation or network connectivity opportunities for MPAs. An alternative is development of one or more regional workgroups of protected area specialists, fishery scientists, expert fishers, and other stakeholders. Temporal closures of fisheries before and during spawning season could also amplify effectiveness of current gear‐ and zoning‐based management tools.